2000
DOI: 10.1046/j.1463-5224.2000.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tear film proteinases in horses with ulcerative keratitis

Abstract: Ulcerative keratitis is a common and potentially blinding ocular disease of horses, capable of progressing to corneal perforation in as little as 24 h. This rapid stromal degeneration is mediated in part by exogenous and endogenous proteinases. We measured and compared the concentrations of two matrix metalloproteinases (MMP-2 and MMP-9) and a serine proteinase (neutrophil elastase) present in the precorneal tear film of normal horses and horses with rapidly progressing ulcerative keratitis. Precorneal tear fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 23 publications
(37 reference statements)
2
60
0
6
Order By: Relevance
“…Acera et al [30] found significantly elevated pro-MMP-9 levels in blepharitis, allergic eye disease, dry eye and conjunctivochalasis. An increased expression of MMP-2 has been demonstrated in chronic inflammatory processes, which can result in the perforation of the cornea in both humans [31] and horses [32,33]. Similarly, the expression of active MMP-2 and -9 correlated with the severity of ulceration or burn trauma [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Acera et al [30] found significantly elevated pro-MMP-9 levels in blepharitis, allergic eye disease, dry eye and conjunctivochalasis. An increased expression of MMP-2 has been demonstrated in chronic inflammatory processes, which can result in the perforation of the cornea in both humans [31] and horses [32,33]. Similarly, the expression of active MMP-2 and -9 correlated with the severity of ulceration or burn trauma [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os diversos fatores aos quais se atribui a elevada incidência de afecções corneais em equinos, elencamse o tamanho do bulbo do olho, seu posicionamento proeminente e lateralizado e atividades físicas dos equinos (STRUBBE et al, 2000;BAKER et al, 2008;WADA et al, 2010). Ainda, a superfície ocular encontrase constantemente exposta a bactérias e fungos.…”
Section: Desenvolvimentounclassified
“…A MMP-9 encontra-se presente após danos corneais, induzindo à destruição de estruturas adesivas da membrana basal das células epiteliais, retardando, por conseguinte, a reepitelização corneal (OLLIVIER et al, 2003;BOVELAND et al, 2010). Em córneas ulceradas, a atividade das proteinases encontra-se significativamente aumentada no filme lacrimal pré-corneal (STRUBBE et al, 2000;OLLIVIER et al, 2004).…”
Section: Desenvolvimentounclassified
See 1 more Smart Citation
“…eine eingeschränkte Sehfähigkeit unter Umständen fatal und kann einen erheblichen wirtschaftlichen Verlust für den Tierhalter bedeuten. Die Therapie von Hornhautulzera stellt eine Herausforderung dar, denn innerhalb kurzer Zeit kann es durch enzymatische Zerstörung des Stromas zu Schäden von großem Ausmaß bis hin zu einer Perforation der Hornhaut kommen (Strubbe et al 2000, Haffner et al 2003, De Linde Henriksen et al, 2012. Eine fundierte Aufklärung der Besitzer hinsichtlich der Behandlungsmöglich-keiten, der Prognose für den Erhalt des Auges und der Sehfä-higkeit sowie der Dauer der Behandlung ist schwierig (Höpp-ner 2007).…”
Section: Introductionunclassified